Glencoe Literature. British Literature - Beverly Ann Chin; Chin, Beverly Ann.; Wolfe, Denny; Copeland, Jeffrey; Dudzinski, Mary Ann.; Ray, William; Royster, Jacqueline Jones; Wilhelm, Jeffrey (McGrmaw Hill Companies,Inc, 2000)
Africa; Ancient Greece and Rome; Southwest and South Central Asia; East Asia and the Pacific; Europe; The Americas.
Keywords: American literature; Literature -- Collections